Mathematics in Culture: Revealing Hidden Secrets Behind Indonesian Traditional Ceremonies - Wangge, Magdalena; Dasari, Dadan; Turmudi, Turmudi (Tematik : Jurnal Konten Pendidikan Matematika, 2025)
Ethnomathematics examines the intersection of mathematics and culture, highlighting how mathematical concepts are embedded within local traditions. In culturally rich Indonesia, ethnomathematics holds increasing relevance. This study examines the presence of mathematical principles in traditional ceremonies, revealing their integration into various cultural elements, including clothing, dances, tools, and rituals. This study employs a systematic literature review (SLR) using the PRISMA approach to analyze 27 articles published between 2018 and 2024. Articles were selected through a structured search and screening process based on predefined inclusion and exclusion criteria. Data collection focused on identifying mathematical concepts in traditional ceremonies, while thematic analysis was used to categorize ethnomathematical patterns in Indonesian cultural practices. Findings highlight common patterns, such as geometric shapes, measurement techniques, and symmetry, which are evident in artifacts, traditional attire, and ceremonial practices. Additionally, the study underscores the variation in mathematical applications across different regions, reflecting Indonesia’s cultural diversity. These insights have significant implications for developing a more contextual and relevant mathematics education. By connecting mathematical concepts with local culture, ethnomathematics enhances student engagement and understanding, making learning more meaningful and culturally grounded. This approach not only enriches mathematical education but also helps preserve and appreciate Indonesia’s unique cultural heritage, promoting a more inclusive and diverse educational framework.